Search for gamma rays from SNe with a variable-size sliding-time-window analysis of the Fermi-LAT data. Issue 1 (10th May 2021) - Prokhorov, D A; Moraghan, A; Vink, J
ABSTRACT: We present a systematic search for γ-ray emission from supernovae (SNe) in the Fermi Large Area Telescope (LAT) Pass 8 data. The sample of targets consists of 55, 880 candidates from the Open Supernova Catalogue . We searched for γ rays from SNe by means of a variable-size sliding-time-window analysis. Our results confirm the presence of transient γ-ray emission from the sources of non-AGN classes, including transitional pulsars, solar flares, γ-ray bursts, novae, and the Crab Nebula, which are projected near some of these SN's positions, and also strengthen support to the variable signal in the direction of SN iPTF14hls. The analysis is successful in finding both short (e.g. solar flares) and long (e.g. transitional pulsars) high flux states. Our search reveals two new γ-ray transient signals occurred in 2019 in the directions of optical transients that are SN candidates, AT2019bvr and AT2018iwp, with their flux increases within 6 months after the dates of SN's discoveries. These signals are bright and their variability is at a higher statistical level than that of iPTF14hls. An exploration of archival multiwavelength observations towards their positions is necessary to establish their association with SNe or other classes of sources. Our analysis, in addition, shows a bright transient γ-ray signal at low Galactic latitudes in the direction of PSR J0205+6449. In addition, we report the results of an all-sky search for γ-ray transient sources. This provided two additional candidates to gamma-ray transient sources.